The role of calcium activated and voltage gated potassium channel BK, in glioblastoma multiforme membrane potential. - Ratnasingham, Mathuscha (2024)
Glioblastoma multiforme (GBM), is an aggressive brain tumour that accounts for nearly half of all glial brain tumours. Large conductance voltage and Ca2+-activated potassium channels, BK, are overexpressed in GBM and are thought to play a role in their invasion and migration. Although changes in resting membrane potential modulate these processes, little is known about the origin of it in GBM and the role of BK. I have used cell-attached and whole-cell patch clamp in the glioblastoma cell lines, SF188 and GCE62 to investigate the role of BK in GMB resting membrane potential. Single channel BK currents were measured with cell-attached patch clamp. Pipettes contained 140 mM K+. Currents were measured with holding potentials from 0 mV to -90 mV. The resting membrane potential of intact cells was estimated from the reversal potential of cell-attached single-channel BK current-voltage (I-V) plots. Resting membrane potential was then measured with current clamp immediately after forming the whole-cell configuration. In SF188s, at a pipette potential of 0 mV, BK was spontaneously active in 31 out of 71 patches. Cell-attached I-V analyses indicated voltage-dependent activation of gBK with a bimodal distribution of median slope-conductance of around 124 and 215 pS. Membrane potential estimated from the cell-attached I-V reversal potential, -35±0.18 mV was similar to that subsequently measured under whole-cell current clamp -35±0.18 mV ([Ca2+] = 120 nM). With high [Ca2+] pipette solution (2.5 mM), membrane potential was significantly hyperpolarized in whole-cell current clamp (-44 ± 17 mV) whereas the input resistance, 220 ± 173 M; was similar to that with low pipette [Ca2+]: 396 ± 173 M. In 100% of cell-attached patches, BK activity was abolished by 10 µM paxilline and 200 µM quinine. With low pipette [Ca2+] whole-cell membrane potential was unaffected by 200 µM quinine but was significantly hyperpolarised by 13 mV with 10 µM paxilline and 9 mV with 1 mM TEA. With low pipette [Ca2+] whole-cell membrane potential was unaffected by Cl- free Hanks but was significantly depolarised by 8 mV with K+ Hanks and hyperpolarised by 8 mV with Na+ free Hanks. In GCE62’s, at a pipette potential of 0 mV, BK was spontaneously active in 2 out of 30 patches. In whole cell current clamp there was no significant difference in the membrane potential and input resistance in the high [Ca2+] pipette solution compared to low [Ca2+] in the pipette solution. GBM SF188 exhibit spontaneous K+ channel activity in cell-attached patches, with biophysical and pharmacological properties typical for BK. At low intracellular [Ca2+] BK does not appear to be responsible for the resting membrane potential. The reversal potential of BK in cell-attached patches appears to be an accurate non-invasive measure of the resting membrane potential of SF188 cells. The membrane potential seems to be predominated by potassium with a degree of sodium. Further studies are required to determine what underlies BK activation in cell-attached patches in SF188 and under what conditions is BK activated to contribute to membrane potential in this cell line.